2014
DOI: 10.1021/nn501896e
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Wear of Amorphous Hydrogenated Carbon during Intermittent Contact: A Combined Study Using Experiment, Simulation, and Theory

Abstract: In this study, we explore the wear behavior of amplitude modulation atomic force microscopy (AM-AFM, an intermittent-contact AFM mode) tips coated with a common type of diamond-like carbon, amorphous hydrogenated carbon (a-C:H), when scanned against an ultra-nanocrystalline diamond (UNCD) sample both experimentally and through molecular dynamics (MD) simulations. Finite element analysis is utilized in a unique way to create a representative geometry of the tip to be simulated in MD. To conduct consistent and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 49 publications
2
58
1
Order By: Relevance
“…These continuum models and their various extensions rely on underlying assumptions that may be violated at nanometer length scales. An alternative to continuum models is atomistic simulations, which are able to track the position of each atom and have been employed to study nanocontacts mimicking experimental conditions [15][16][17][18][19]. Some such simulations have suggested that contact mechanics may be applied when atomic-scale surface roughness is considered in the model [20] or when modifications of these theories are used, such as thin-coating contact mechanics [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…These continuum models and their various extensions rely on underlying assumptions that may be violated at nanometer length scales. An alternative to continuum models is atomistic simulations, which are able to track the position of each atom and have been employed to study nanocontacts mimicking experimental conditions [15][16][17][18][19]. Some such simulations have suggested that contact mechanics may be applied when atomic-scale surface roughness is considered in the model [20] or when modifications of these theories are used, such as thin-coating contact mechanics [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…In general, ultrathin amorphous carbon films have gathered great technological interest as overcoats for magnetic storage devices, MEMS/NEMS, and AFM tips, owing to their excellent mechanical and tribological properties, and the capability for room‐temperature deposition . However, at the ultrathin film level, the role of the substrate and the film–substrate (FS) interface also become very important, and the wear and friction mechanisms at this level are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite extensive study, these wear studies have produced only empirical relationships between mechanical load and film chemistry, due in part to poor chemical definition of the starting material, film inhomogeneity and environmental contaminants 10 . Consequently, there has been a growing interest in using nanometre scale, single asperity sliding contacts to probe mechanochemical bond scission at the tip-substrate interface, and recent work has shown volumetric resolution approaching a few atoms 11,12 . It remains unclear, however, what role surface topography plays, which bond or bonds are being broken and which properties-length, energy, polarization and so on-of the bond are important.…”
mentioning
confidence: 99%